Activation energy, Temperature Coefficient and Q10 Value Estimations of the Growth of Serratia marcescens strain DRY6 on SDS (Journal of Environmental Microbiology and Toxicology, 2022)
Sodium dodecyl sulfate, occasionally known as SDS, is a widely used anionic surfactant globally as a foaming component in a wide variety of cleaning products, including shampoos, toothpaste, and detergents. Large quantities of SDS are released into the environment despite the fact that they are hazardous and have the ability to create foam. This can lead to problems in sewage treatment facilities. There are a few different models that may be utilized to mimic the growth rate of microbes on a variety of different medium at various temperature. Arrhenius is one of the most often used models partly since it has a small number of parameters. Temperature frequently influences the progress and metabolic activities of microbes on the substrates they are growing on. Because of their small size, microbes are very sensitive to variations in temperature. In order to describe the development of Serratia marcescens strain DRY6 on SDS, a discontinuous apparent activation energy with a chevron-like graph was used, and the graph's break point was set at 28.05 degrees Celsius. Following the completion of the regression study, two activation temperatures were established: 20-27 degrees Celsius and 30-42 degrees Celsius, with respective activation energies of 41.72 and 84.72 kilojoules per mole. Within the temperature range that was taken into account, it was projected that the Q10 value would be 2.905, and the theta value would be 1.11. (30-42 oC). This study is especially helpful in projecting SDS breakdown and migration during bioremediation because of its comprehensive nature.
Keywords: SDS-degrading; Serratia marcescens strain DRY6; Temperature; Arrhenius plot; Breakpoint